REGIONAL DEVELOPMENT - PAST, PRESENT AND FUTURE IN ROMANIA - SIMONA BIRIESCU; ANTOANETA BUTUZA (Annals of the University of Petrosani: Economics)
Romania's participation in the implementation of EU regional policy means, first opportunity to benefit from a system of values that can be found between economic efficiency, environmental protection,ensuring minimum standards of existence, the definition of a "European lifestyle, urban values, qualified human resources. Moreover, European integration and openness to the EU internal market and the challenge involves increasing competitiveness, which can negatively affect the process of building an economy, like Romania. In this context, structural instruments are the most important resource that Romania will have to face the challenges of change and integration. However, regional development policy can not solely be the key to overall development of a state, especially in terms of its actual effects on growth are difficult to assess. A critical dimension of this is represented on the nature of economic and quality of other public policies that form the core of economic policy mix of a state: the legal protection of property rights and market economy, taxation, antitrust, etc.